2016
DOI: 10.1128/jvi.01245-16
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptional Analysis of Virus-Host Interactions between Phage ϕ29 and Bacillus subtilis

Abstract: The study of phage-host relationships is essential to understanding the dynamic of microbial systems. Here, we analyze genomewide interactions of Bacillus subtilis and its lytic phage 29 during the early stage of infection. Simultaneous high-resolution analysis of virus and host transcriptomes by deep RNA sequencing allowed us to identify differentially expressed bacterial genes. Phage 29 induces significant transcriptional changes in about 0.9% (38/4,242) and 1.8% (76/4,242) of the host protein-coding genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 69 publications
5
42
0
Order By: Relevance
“…fitness in the presence of diverse phages ( Supplementary Table S4). How the down-regulation of host tRNA and tRNA modification genes impact host fitness, phage growth and infection cycle is not clear, although recent studies have shown increased aminoacyl-tRNA synthetase activities in the early phage infection cycle [125,126].…”
Section: A Crispri Screen Provides Deeper View Of Phage Resistance Dementioning
confidence: 99%
“…fitness in the presence of diverse phages ( Supplementary Table S4). How the down-regulation of host tRNA and tRNA modification genes impact host fitness, phage growth and infection cycle is not clear, although recent studies have shown increased aminoacyl-tRNA synthetase activities in the early phage infection cycle [125,126].…”
Section: A Crispri Screen Provides Deeper View Of Phage Resistance Dementioning
confidence: 99%
“…A few studies have recently reported findings of phage–host interactions using transcriptomic and metabolomic approaches in P. aeruginosa , Yersinia enterocolitica, Bacillus subtilis , and the marine microbe Sulfitobacter sp. 2047 (Lavigne et al, 2013; Ankrah et al, 2014; Chevallereau et al, 2016; De Smet et al, 2016; Leskinen et al, 2016; Mojardin and Salas, 2016). Chevallereau et al (2016) used next-generation “omics” approaches to investigate the interactions between P. aeruginosa and bacteriophage PAK_P3 and found that RNA processing was hijacked by phage infection and that bacterial transcripts were significantly depleted.…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory antisense RNAs have been observed in lambda phage (Krinke et al, 1991), bacteriophage 186 (Dodd and Egan, 2002), P22 (Liao et al, 1987), and T4 (Belin et al, 1987). Antisense RNA has been detected in phage ϕ29 (Mojardín and Salas, 2016) and AR9 (Lavysh et al, 2017) but no definitive function has been yet assigned.…”
Section: Discussionmentioning
confidence: 99%